Negotiating multisectoral evidence: a qualitative study of knowledge exchange at the intersection of transport and public health - Cornelia Guell; Roger Mackett; David Ogilvie (BMC, 2017)
Abstract Background For the prevention and control of chronic diseases, two strategies are frequently highlighted: that public health should be evidence based, and that it should develop a multisectoral approach. At the end of a natural experimental study of the health impacts of new transport infrastructure, we took the opportunity of a knowledge exchange forum to explore how stakeholders assessed, negotiated and intended to apply multisectoral evidence in policy and practice at the intersection of transport and health. We aimed to better understand the challenges they faced in knowledge exchange, as well as their everyday experiences with working in multisectoral remits. Methods In 2015, we conducted participant observation during an interactive event with 41 stakeholders from national and local government, the third sector and academia in Cambridge, UK. Formal and informal interactions between stakeholders were recorded in observational field notes. We also conducted 18 semistructured interviews reflecting on the event and on knowledge exchange in general. Results We found that stakeholders negotiated a variety of challenges. First, stakeholders had to negotiate relatively new formal and informal multisectoral remits; and how to reconcile the differing expectations of transport specialists, who tended to emphasise the importance of precedence in guiding action, and health specialists' concern for the rigour and synthesis of research evidence. Second, research in this field involved complex study designs, and often produced evidence with uncertain transferability to other settings. Third, health outcomes of transport schemes had political traction and were used strategically but not easily translated into cost-benefit ratios. Finally, knowledge exchange meant multiple directions of influence. Stakeholders were concerned that researchers did not always have skills to translate their findings into understandable evidence, and some stakeholders would welcome opportunities to influence research agendas. Conclusions This case study of stakeholders' experiences indicates that multisectoral research, practice and policymaking requires the ability and capacity to locate, understand and communicate complex evidence from a variety of disciplines, and integrate different types of evidence into clear business cases beyond sectoral boundaries.